Does Facebook usage lead to conspicuous consumption? The role of envy, narcissism and self-promotion. Issue 3 (8th August 2016) - Taylor, David G.; Strutton, David
Abstract : Purpose: The purpose of this study is to demonstrate how Facebook usage is positively related to envy and narcissism, which in turn increase users' desire for self-promotion and propensity to engage in conspicuous consumption. Design/methodology/approach: Data were collected via an online survey, with 674 usable responses collected from Facebook users of all ages. Findings: The results support the hypotheses that increased Facebook usage is positively related to envy and narcissism. These two psychological constructs lead to stronger desires for self-promotion, spurring the behavioral response of conspicuous online consumption. Research limitations/implications: The findings are limited to the self-reported behaviors of a limited sample. Despite the limitations, the findings identify a process by which increased Facebook usage results in an increased desire to promote oneself through conspicuous consumption. Practical implications: An understanding of the psychology linking social media use to conspicuous consumption can aid managers in developing marketing strategies to encourage the purchase and usage of positional goods. Specifically, more frequent users may be targeted by advertisers wishing to encourage the purchase and display of their products. Originality/value: An emerging stream of research suggests that social media usage elicits both positive self-comparisons with others (i.e. narcissism) and negative (i.e. envy). This study is among the first to empirically test this effect on the purchase and consumption of positional goods.